Investigation of the Morpho-Anatomical and Epidermal Properties of Commelina erecta L. - C. Wahua; R. B. Peter (Journal of Applied Sciences and Environmental Management, 2024)
In traditional medicine, Commelina erecta L. has been used as antiviral, for the treatment of hemorrhages, skin rashes and sores, and for the treatment of infections. It is also used as a wild edible plant in salads, preserves or decorating the dishes. Hence, the objective of this paper was to investigate the morpho-anatomical and epidermal properties of Commelina erecta L of Commelinaceae using appropriate standard methods. Results revealed C. erecta as a Broadleaf and vivacious branching up to 20 to 55 cm in length as it trails and roots at nodes, having leaves which are elliptical, oval to lanceolate and sub sessile about 2.5 ± 0.5 cm long and 1.5 ± 0.5 cm wide; the leaf sheath is closed and united at base. The stomata are anomocytic, tetracytic and paracytic stomata with pentagonal to heptagonal epidermal cells and trichomes (piloses) including glandular trichomes which are amphistomatic. Anatomical sections showcased root pith, vascular bundles scattered and concentrated towards the ground tissues. These information would assist for further delimitation of the species.